1999
DOI: 10.1086/302327
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Haplotype Studies of Familial Mediterranean Fever Reveal New Ancestral Relationships and Evidence for a High Carrier Frequency with Reduced Penetrance in the Ashkenazi Jewish Population

Abstract: Familial Mediterranean fever (FMF) is a recessive disorder characterized by episodes of fever with serositis or synovitis. The FMF gene (MEFV) was cloned recently, and four missense mutations were identified. Here we present data from non-Ashkenazi Jewish and Arab patients in whom we had not originally found mutations and from a new, more ethnically diverse panel. Among 90 symptomatic mutation-positive individuals, 11 mutations accounted for 79% of carrier chromosomes. Of the two mutations that are novel, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
4
7

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 264 publications
(233 citation statements)
references
References 24 publications
(43 reference statements)
11
209
4
7
Order By: Relevance
“…When FMF was first discovered, it was shown that homozygosity for p.M694V was associated with more severe disease, including early onset, more frequent attacks, significantly more joint disease, a higher dose of colchicine needed to control attacks, and a higher rate of amyloidosis among patients not adequately treated (28). These results were confirmed in further studies performed in Israel, France (with Armenian patients), and in Middle Eastern countries (Jordan and Lebanon) (22)(23)(24). However, some studies from Turkey were not in agreement with these results, but many recent studies from this country do show similar results (5,29 -31).…”
Section: Clinical Manifestations Of Fmf In Various Populationsmentioning
confidence: 74%
See 1 more Smart Citation
“…When FMF was first discovered, it was shown that homozygosity for p.M694V was associated with more severe disease, including early onset, more frequent attacks, significantly more joint disease, a higher dose of colchicine needed to control attacks, and a higher rate of amyloidosis among patients not adequately treated (28). These results were confirmed in further studies performed in Israel, France (with Armenian patients), and in Middle Eastern countries (Jordan and Lebanon) (22)(23)(24). However, some studies from Turkey were not in agreement with these results, but many recent studies from this country do show similar results (5,29 -31).…”
Section: Clinical Manifestations Of Fmf In Various Populationsmentioning
confidence: 74%
“…However, Jews of North African origin have only the mutations p.M694V and p.E148Q, whereas Ashkenazi Jews carry only the mutations p.E148Q and p.V726A. It seems that these 3 mutations are very ancient and appeared in the Middle East (Mesopotamia) more than 2,500 years ago (22). Mutation p.M694V migrated to Spain and North Africa either in the early days via sailors (Phoenicians) who crossed the Mediterranean Sea from the Middle East or later (in the 8th century) via land migration westward during the Muslim conquest of North Africa and Spain (Figure 1).…”
Section: Distribution Of Mefv Mutations In Fmf Patients Around the Worldmentioning
confidence: 99%
“…Consistent with this hypothesis human population studies revealed extremely high allele frequencies for several different pyrin mutations, leading to the conclusion that the mutant alleles confer a selective advantage. [42][43][44] It was also reported that some of the very same amino acids mutated in FMF carriers are often present as WT in primates and other species. 16 The recently reported data that mice expressing a C-terminal truncated version of pyrin have a heightened sensitivity to endotoxic shock and an increased caspase-1 activation and IL-1b production in macrophages from these mice after stimulation, 11 is not inconsistent with our model.…”
Section: Discussionmentioning
confidence: 92%
“…126 The disease carrier rate in some populations may be extremely high as one in seven. 133,134 This may reflect a founder effect or some unknown selective pressure, conferring an advantage to the heterozygote carriers. This is possibly the consequence of some environmental or localized infectious diseases that may have affected population around the Mediterranean Sea.…”
Section: Regulators Of Inflammatory Caspase Activationmentioning
confidence: 99%